The Promises and Challenges of Artificial Intelligence for Higher Secondary Teachers: A Systematic Review of Research (International Journal of Food and Nutritional Sciences, 2022)
Artificial intelligence (AI) is turning out to be more basic in numerous regions of the economy, including secondary schooling. Lately, the field of AIin Schooling Improvement has seen significant progressions. This study planned to research the utilization of AI in optional schooling for educating and learning purposes, as well as the impacts of involving AI in this unique circumstance.This study explores the educational consequences of rapidly changing technology on the processes and scope of learning and instruction.Artificial intelligence enables secondary education services to be quickly and conveniently available, both inside and outside the confines of the classroom.This research aims to explore the integration of AI into secondary teachers and assess its immediate and future repercussions on many aspects of secondary education.The difficulties in deploying artificial intelligence in these institutions were also examined.This research aims to effectively supply educators with rich information and in-depth understanding for establishing educational models, hence creating prospects for future progress.